PjBL with Smart Board Media to Support Elementary Students’ Learning Outcomes in Natural and Social Sciences: A Case Study at SDN 01 Gumeng Karanganyar - Rahma Liya Putri; Anggit Grahito Wicaksono; Dite Hastini (Program Studi PGSD Universitas Madako Tolitoli, 2026)
Limited student engagement and uneven conceptual understanding in elementary Natural and Social Sciences learning remain persistent challenges, particularly when instruction relies on conventional methods with minimal technological integration. This study aimed to examine the implementation of Project-Based Learning (PjBL) supported by Smart Board technology in enhancing student engagement and conceptual understanding among fifth-grade learners at SDN 01 Gumeng, Karanganyar. This study uses a descriptive qualitative design with a naturalistic case study design, with data collection through classroom observation, interviews, and documentation, and validated through triangulation techniques. The findings indicate that the PjBL model was implemented systematically across its six stages, resulting in observable improvements in student participation, collaboration, and conceptual clarity. Interactive Smart Board features facilitated visual engagement and supported active learning, with most students demonstrating increased involvement during project activities. However, constraints such as limited instructional time, insufficient technological infrastructure, and diverse student ability levels affected the consistency of implementation. This study implies that integrating PjBL with interactive technology can strengthen student-centered learning practices and offers practical insights for improving instructional design in primary education contexts.